Status of solar desalination in India - Arjunan, T. V.; Aybar, H. S.; Nedunchezhian, N. (Pergamon-Elsevier Science Ltd, 2009)
The work was motivated by the increasing awareness of the need for enhancing water supplies schemes in and lands featuring an appropriate technology for solar energy use in the desalination field in India. The fresh water crisis is already evident in many parts of India, varying in scale and intensity at different times of the year. India's rapidly rising population and changing lifestyles also increases the need for fresh water. Fresh water is increasingly taking centre stage on the economic and political agenda, as more and more disputes between and within states, districts, regions, and even at the community level arises. The conventional desalination technologies like multi stage flash, multiple effect, vapor compression, iron exchange, reverse osmosis, electro dialysis are expensive for the production of small amount of freshwater, also use of conventional energy sources has a negative impact on the environment. Solar distillation represents a most attractive and simple technique among other distillation processes, and it is especially suited to small-scale units at locations where solar energy is considerable. India, being a tropical country is blessed with plenty of sunshine. The average daily solar radiation varies between 4 and 7 kWh per square meter for different parts of the country. There are on an average 250-300 clear sunny days in a year, thus it receives about 5000 trillion kWh of solar energy in a year. In spite of the limitations of being a dilute source and intermittent in nature, solar energy has the potential for meeting and supplementing various energy requirements. Solar energy systems being modular in nature could be installed in any capacity as per the requirement. This paper consists of an overall review and technical assessments of various passive and active solar distillation developments in India. This review also recommended some research areas in this field leading to high efficiency are highlighted. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Distillation; Fresh water; Economic; Research; Solar energy